PELATIHAN MEDIA PEMBELAJARAN K-VISOFT FLIPBOOK MAKER UNTUK MENINGKATKAN KETERAMPILAN LITERASI DIGITAL MAHASISWA FKIP UNIVERSITAS ASAHAN - Rafika Muspita Sari; Oktaviana Nirmala Purba; Karimaliana; Mapilindo; Yen Aryni (Jurnal Pemberdayaan Sosial dan Teknologi Masyarakat, 2026)
The development of digital technology has brought significant changes to the world of education, particularly in the development of technology-based learning media. Students, as the digital generation, are required to have adequate digital literacy skills to effectively utilize technology in the learning process. One learning medium that can support digital literacy is K-Visoft Flipbook Maker, software that can convert digital documents into interactive e-books. This Community Service (PKM) activity aims to improve the digital literacy skills of FKIP Asahan University students through training on the use of K-Visoft Flipbook Maker. The methods used included preparation, training implementation, mentoring, and evaluation. Forty FKIP Asahan University students participated in the activity. The results showed an increase in students' abilities in developing digital learning media. The average pretest score of 62.4 increased to 86.7 in the posttest. This 24.3-point increase demonstrates the effectiveness of the training in improving students' digital literacy skills. Furthermore, students were able to produce interactive flipbooks that can be used as learning media. Thus, the K-Visoft Flipbook Maker training was effective in improving students' digital literacy skills.